2011
DOI: 10.1590/s1807-59322011000700006
|View full text |Cite
|
Sign up to set email alerts
|

A sigmoidal fit for pressure-volume curves of idiopathic pulmonary fibrosis patients on mechanical ventilation: clinical implications

Abstract: OBJECTIVE:Respiratory pressure-volume curves fitted to exponential equations have been used to assess disease severity and prognosis in spontaneously breathing patients with idiopathic pulmonary fibrosis. Sigmoidal equations have been used to fit pressure-volume curves for mechanically ventilated patients but not for idiopathic pulmonary fibrosis patients. We compared a sigmoidal model and an exponential model to fit pressure-volume curves from mechanically ventilated patients with idiopathic pulmonary fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…These changes in lung structure lead to a severe impairment of lung function related to a decreased elasticity. Indeed, increased lung elastance as well as decreased compliance (the reciprocal of elastance) have been shown in humans (19,26,38) and in small rodent pulmonary fibrosis models (1,7,12,15,30,53,57,58). Moreover, changes in tidal volume and breathing cycle times have been shown in a mouse fibrosis model (33).…”
mentioning
confidence: 99%
“…These changes in lung structure lead to a severe impairment of lung function related to a decreased elasticity. Indeed, increased lung elastance as well as decreased compliance (the reciprocal of elastance) have been shown in humans (19,26,38) and in small rodent pulmonary fibrosis models (1,7,12,15,30,53,57,58). Moreover, changes in tidal volume and breathing cycle times have been shown in a mouse fibrosis model (33).…”
mentioning
confidence: 99%
“…It has been observed that Equation (6) also provide good fits to the P – V curve of both fibrotic (Ferreira et al, 2011 ) and emphysematous (Soutiere and Mitzner, 2004 ; Pérez-Rial et al, 2014 ) lungs. The altered P – V curves in these diseases can thus be mimicked simply by adjusting the parameters in Equation (6).…”
Section: Applying the Model To Fibrotic And Emphysematous Lungsmentioning
confidence: 97%
“…Following the results observed in Ferreira et al ( 2011 ), Soutiere and Mitzner ( 2004 ), and Pérez-Rial et al ( 2014 ), we model fibrosis by increasing b , while emphysema is modeled by decreasing b . Specifically, we let b vary with disease state according to where c is the fraction of lung parenchymal tissue affected by disease (a measure of disease severity), b 0 is the value of b for a healthy lung, and f ( c ) is a dimensionless function capturing the influence of the disease.…”
Section: Applying the Model To Fibrotic And Emphysematous Lungsmentioning
confidence: 97%
“…The first term V el represents the volume due to aggregate elasticity of the lung unit structure, which is modeled here as a saturated exponential [ 26 28 ] where k characterizes the lung stiffness. This representation has been found to suffice in cases of a healthy or surfactant-treated lung.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Both scenarios indicate a lower compliance and greater pressure required to increase the lung volume in the region of operating pressure. In certain pathological situations such as ARDS, a sigmoidal representation of V A ( P el ) with a low compliance region at low P el [ 28 , 31 34 ] could be captured in the parameterization of F rec .…”
Section: Mathematical Modelmentioning
confidence: 99%